2002
DOI: 10.1136/jcp.55.8.619
|View full text |Cite
|
Sign up to set email alerts
|

Human herpesvirus 8 (HHV-8) detected in two patients with Kaposi's sarcoma-like pyogenic granuloma

Abstract: Aims: To report the finding of human herpesvirus 8 (HHV-8) in two patients with Kaposi's sarcoma (KS)-like pyogenic granuloma. This form of pyogenic granuloma closely resembles KS histologically and it has been reported that immunohistochemistry in such lesions may be positive for smooth muscle actin and factor VIII related antigen, which are typically negative in KS. In both patients the lesions were positive for CD31, CD34, smooth muscle actin, and factor VIII related antigen, a profile typical of KS-like py… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0
2

Year Published

2005
2005
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 24 publications
0
26
0
2
Order By: Relevance
“…The great majority of non-Kaposi sarcoma vascular tumors previously studied have, however, been negative for HHV-8 by PCR. 16,[27][28][29][30][31][32][33] Given that the positive cases in the present study all showed levels above our preset high threshold level, we believe our results do indicate the true presence of HHV-8, rather than representing 'false positives'. Regrettably, we did not have access to frozen tissue from these positive cases, and thus were unable to perform Southern blot confirmation.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…The great majority of non-Kaposi sarcoma vascular tumors previously studied have, however, been negative for HHV-8 by PCR. 16,[27][28][29][30][31][32][33] Given that the positive cases in the present study all showed levels above our preset high threshold level, we believe our results do indicate the true presence of HHV-8, rather than representing 'false positives'. Regrettably, we did not have access to frozen tissue from these positive cases, and thus were unable to perform Southern blot confirmation.…”
Section: Discussionmentioning
confidence: 63%
“…26 Our finding of uniform HHV-8 expression in Kaposi sarcoma, by PCR, is in agreement with numerous prior studies, all of which have found 490% of Kaposi sarcoma of all types to be HHV-8 positive, using both traditional and in situ PCR. 16,[27][28][29][30][31][32][33] The 100% detection rate we observed may in part be due to our use of a high cycles-tothreshold limit of 50. We chose to carry reactions out to 50 cycles-to-threshold for the purpose of detecting potentially very low viral loads in paraffinembedded tissue blocks that had been in storage for up to 10 years.…”
Section: Discussionmentioning
confidence: 99%
“…Apart from heightened awareness and recognition of the changing face of KS in the AIDS era, diagnostic confirmation has also been facilitated by the relative recent discovery of Human herpesvirus-8 (HHV8), also labelled KS-associated herpes virus, as the viral etiopathogenesis of KS [17]. This has facilitated improved understanding of KS and therapeutic possibilities and distinction from diagnostic masqueraders [17][18][19][20][21][22][23]. The commercial availability of HHV-8 LANA-1 immunohistochemical antibodies and HHV8 PCR studies has enabled the diagnostic confirmation of KS in challenging histodiagnostic settings [19][20][21][22].…”
Section: Discussionmentioning
confidence: 99%
“…This has facilitated improved understanding of KS and therapeutic possibilities and distinction from diagnostic masqueraders [17][18][19][20][21][22][23]. The commercial availability of HHV-8 LANA-1 immunohistochemical antibodies and HHV8 PCR studies has enabled the diagnostic confirmation of KS in challenging histodiagnostic settings [19][20][21][22]. HHV-8 LANA-1 is a nuclear immunohistochemical antigen that is expressed by all cells that are latently infected by the virus.…”
Section: Discussionmentioning
confidence: 99%
“…Baz› piyojenik granülom benzeri KS olgular›nda KS'nun tan›sal özelliklerinin hiçbiri görülmeyebi-lir. Bu olgularda HHV8 immün reaksiyonunun gösterilmesi tan›y› destekler 25,26 . Urguhart ve ark., bu histolojik alt tipin iyi s›-n›rl›, epidermisin yakal›k tarz›nda lezyonu çevreledi¤i, iyi geliflmifl kapillerlerin eksofitik proliferasyonu olarak tan›mla-maktad›r 16 .…”
Section: Tart›flmaunclassified